Quantitative - Spatial Analysis of Soil Loss by Laminar Erosion and Comparison with NDVI Method of the Municipalities of Mandaguaçu and Presidente Castelo Branco / PR - Uema, Diogo Yukio; Eduvirgem, Renan Valério; Santil, Fernando Luiz de Paula (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
Environmental monitoring is essential for society to maintain balance with the environment, given this fact, several methods from the science of geoprocessing and remote sensing were created to assist in the task. The present work used the Universal Soil Loss Equation to verify the spatiality of laminar erosions in the municipalities of Mandaguaçu and Presidente Castelo Branco, both in Paraná, in addition to comparing their results with data from the Digital Vegetation Index (NDVI) to obtain relationships between the loss of soils and the development or lack of vegetation. The results identified several foci of laminar erosion in the study area, as a possible cause, soils from the highly erodible Caiuá Sandstone can be considered, as well as topographic factors of the EUPS LS factor. It should be noted that the use of digital tools, satellite images and map algebra is not essential for environmental monitoring studies.